Evaluating Medical Interns' Knowledge and Attitudes About Metabolic and Bariatric Surgery - Mozhdeh Mojtahedi; Tooraj Zandbaf; Narges Mesbah; Mohammad Javad Ghamari; Seyed Mohammad Ali Raisolsadat; Ali Mirsadeghi; Yalda Ravanshad (Future of Medical Education Journal)
Background: Recently, Bariatric and Metabolic Surgery (MBS) has received much attention for weight loss and treatment of obesity-related comorbidities. Since attitudes about health care are often formed during medical education and the level of knowledge about MBS among general practitioners is still not satisfactory, there is a need to improve general practitioners' awareness.  This study aimed to investigate the knowledge and attitude of medical internship students of Islamic Azad University, Mashhad Medical Sciences Unit, towards MBS in 2022.Method: All medical interns of Islamic Azad University, Mashhad Medical Sciences Unit, were included in this cross-sectional study. A researcher-made questionnaire including 15 questions, was used. This questionnaire was first translated into Persian. To check the content validity and reliability of the questionnaire, a working group consisting of seven academic surgeons was formed, and the items were reviewed and modified, and after confirming the reliability and validity the questionnaires were provided to the students using Google Forms, and the data were analyzed through SPSS version 16.Results: 105 participants with an average age of 26.49 ± 8.8 years were included, of which 31 were men and 74 were women. The level of knowledge about MBS in interns was favorable. The attitude of interns towards MBS according to gender and body mass index and passing the surgical course did not show any significant difference (p-value>0.05).Conclusion: This research showed that medical interns' knowledge and attitude regarding the characteristics and complications of MBS are generally favorable.